2008
DOI: 10.1002/pc.20653
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable nanocomposites from maleated polycaprolactone/soy protein isolate blend with organoclay: Preparation, characterization, and properties

Abstract: New biobased, eco‐friendly nanocomposites were prepared from maleated polycaprolactone/soy protein isolate blend (50/50 wt/wt) with organo‐modified clay by melt compounding. The XRD, TEM, tensile, DMTA, and rheological properties of the nanocomposites were investigated. X‐ray diffraction and transmission electron microscopy analysis revealed that the intercalated nanocomposite is formed and the silicate layers of the clay are uniformly dispersed at a nanometer scale in the polymer matrix. There is a great enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…This increase was attributed to restricted segmental motion of biopolymer chains in bio‐nanocomposites. Similar results on increase in E ′ and T g of bio‐nanocomposites based on other biopolymers have been reported (Ray and others 2002b; Huang and Netravali 2006; Sasmal and others 2008; Romero and others 2009).…”
supporting
confidence: 88%
“…This increase was attributed to restricted segmental motion of biopolymer chains in bio‐nanocomposites. Similar results on increase in E ′ and T g of bio‐nanocomposites based on other biopolymers have been reported (Ray and others 2002b; Huang and Netravali 2006; Sasmal and others 2008; Romero and others 2009).…”
supporting
confidence: 88%
“…[26] Nayak et al reported that SPI nanocomposites prepared by the melt mixing process exhibit high shearthinning behavior. [27,28] MMT nanoparticles improve the functional behavior of SPI/MMT nanocomposites. [29] SPC/MMT nanocomposite exhibits poor adhesion but excellent structural properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, endowing a surface of implanted medical devices, daily commodities, or equipment with antimicrobial property is extremely necessary in the applications of health care, packaging, water purification, marine biofouling, and textile industry . For this purpose, various antimicrobial materials have been increasingly developed mainly focusing on the introduction of some antibacterial moieties into matrix material, including metal and metal oxides, hybrid particles, quaternary ammonium salts, synthetic, and natural polymers . Particularly, silver nanoparticles (AgNPs) have received extensive attention owing to their wide and extremely effective antimicrobial activity toward various fungi, bacteria, and viruses.…”
Section: Introductionmentioning
confidence: 99%